2009
DOI: 10.1073/pnas.0909235107
|View full text |Cite
|
Sign up to set email alerts
|

IL-4-induced transcription factor NFIL3/E4BP4 controls IgE class switching

Abstract: IL-4 signaling promotes IgE class switching through STAT6 activation and the induction of Ig germ-line ε (GLε) transcription. Previously, we and others identified a transcription factor, Nfil3, as a gene induced by IL-4 stimulation in B cells. However, the precise roles of nuclear factor, IL-3-regulated (NFIL3) in IL-4 signaling are unknown. Here, we report that NFIL3 is important for IgE class switching. NFIL3-deficient mice show impaired IgE class switching, and this defect is B-cell intrinsic. The induction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
139
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 154 publications
(148 citation statements)
references
References 50 publications
8
139
0
1
Order By: Relevance
“…This is consistent with earlier data demonstrating different binding affinities of STAT6 for the ε (high affinity) and g1 (low affinity) promoter (27). Control PCRs diagnosing promoter regions of IgG2a (Ig2a) and of a proteasome gene, (Pr) (21,22), which lack STAT6 binding sites, did not generate signals (Fig. 4A, 4B).…”
Section: Efficient Stat6 Binding and Prevention Of Bcl6 Binding To I«supporting
confidence: 81%
See 2 more Smart Citations
“…This is consistent with earlier data demonstrating different binding affinities of STAT6 for the ε (high affinity) and g1 (low affinity) promoter (27). Control PCRs diagnosing promoter regions of IgG2a (Ig2a) and of a proteasome gene, (Pr) (21,22), which lack STAT6 binding sites, did not generate signals (Fig. 4A, 4B).…”
Section: Efficient Stat6 Binding and Prevention Of Bcl6 Binding To I«supporting
confidence: 81%
“…Some factors are newly synthesized within about a day after IL-4 signaling and depend on STAT6. De novo protein synthesis is not required for induction of NFIL3 transcription, shown to be important for Iε activation and thus for the switch to IgE (22). NFIL3's activity on Iε also depends on STAT6.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Primer sequences for germline transcripts (GLT; g 1 and ε GLT), ε postswitch transcripts, and AID were as described (23). Additional primer sequences were as described: BCL6 (24), Blimp-1 (24), Pax5 (25), Id2 (13), E2A (26), IRF4 (26), NFIL3 (27), Cyclin D2 (28), and CD23 (29). b-actin was used as relative expression control to normalize sample variation.…”
Section: Real-time Pcrmentioning
confidence: 99%
“…In E4bp4 knockout mice, it has been shown that E4BP4 is critical for NK cell development and IgE expression in B cells (12)(13)(14). In addition to its role in the immune system, E4bp4 is also highly expressed in the liver, adipose tissue, and the suprachiasmatic nuclei of the hypothalamus (15).…”
mentioning
confidence: 99%